2023
DOI: 10.1503/cmaj.220637
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of endometriosis

Abstract: Endometriosis is a common disorder that can cause pelvic pain and infertility, may involve multiple organ systems and can adversely affect quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 58 publications
0
34
0
1
Order By: Relevance
“…Despite the increasing body of evidence demonstrating similarities between EAP and other chronic pain conditions, relatively few studies have considered these types of therapies either alone or as a component of a multidisciplinary pain management programme. This is disappointing given that there is evidence of benefit in chronic pelvic pain more generally [1,32].…”
Section: Multidisciplinary Carementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increasing body of evidence demonstrating similarities between EAP and other chronic pain conditions, relatively few studies have considered these types of therapies either alone or as a component of a multidisciplinary pain management programme. This is disappointing given that there is evidence of benefit in chronic pelvic pain more generally [1,32].…”
Section: Multidisciplinary Carementioning
confidence: 99%
“…Endometriosis is defined as the presence of tissue resembling the endometrium outside of the uterus and affects one in 10 women of reproductive age, and an unknown number of trans-men, nonbinary and sex diverse people [1]. It is important to be aware that symptoms often start in adolescence and may not stop after reproductive age, continuing beyond the menopause for some.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis affects more than 176 million women globally (3). Pelvic endometriosis is primarily classi ed as super cial peritoneal endometriosis, deep endometriosis, and ovarian endometrioma (4). Despite the high prevalence of endometriosis, diagnosing the condition remains challenging, with 65% of women being initially misdiagnosed (5).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have helped quantify the socioeconomic impact and quality of life of women affected by endometriosis [2][3][4][5][6][7][8]. This research has revealed not only the substantial financial burden associated with endometriosis but also highlighted the importance of holistic approaches that consider not only medical aspects but also the social and psychological impacts of this condition.…”
Section: Introductionmentioning
confidence: 99%